2022
DOI: 10.2903/j.efsa.2022.7681
|View full text |Cite
|
Sign up to set email alerts
|

Safety evaluation of the food enzyme phytepsin from Cynara cardunculus L.

Abstract: The food enzyme phytepsin (EC 3.4.23.40) is extracted from the pistils of the cardoon Cynara cardunculus L. by ABIASA. It is intended to be used in milk processing for cheese production. As no concerns arose from the source of the food enzyme, from its manufacture, and based on the history of safe use and consumption, the Panel considered that toxicological data and the estimation of dietary exposure were not required. The Panel considered that allergic reactions to this phytepsin cannot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…As a probiotic-rich fungus, Aspergillus oryzae enhances gut health by promoting digestion, boosting immunity, and supporting healthy weight management [37], [30]. Moreover, by enhancing nutrient bioavailability and reducing levels of anti-nutritional agents, Aspergillus oryzae improves the nutritional quality of food products [38], [39] [30]. A study reported that rice bran fermented with Aspergillus oryzae exhibited elevated levels of bioactive compounds and antioxidant potential, with both antioxidant qualities and phenolic group counts increasing during the fermentation process [40].…”
Section: The Predominant Utilized Fungi In Indonesian Traditional Foodmentioning
confidence: 99%
“…As a probiotic-rich fungus, Aspergillus oryzae enhances gut health by promoting digestion, boosting immunity, and supporting healthy weight management [37], [30]. Moreover, by enhancing nutrient bioavailability and reducing levels of anti-nutritional agents, Aspergillus oryzae improves the nutritional quality of food products [38], [39] [30]. A study reported that rice bran fermented with Aspergillus oryzae exhibited elevated levels of bioactive compounds and antioxidant potential, with both antioxidant qualities and phenolic group counts increasing during the fermentation process [40].…”
Section: The Predominant Utilized Fungi In Indonesian Traditional Foodmentioning
confidence: 99%
“…Mice were daily treated orally with 50 μg/kg body weight (bw) per day of BPA or vehicle alone (corn oil) as the control group for 19 days. It was set that dose of BPA since the Environmental Protection Agency (US EPA) had initially established a tolerable daily BPA intake (TDI) of 50 μg/kg bw per day (US EPA, O., 1988), even knowing that EFSA has currently established at 0.2 ng/kg bw per day (EFSA CEP Panel, 2023). Double oral gavage was administered 14 days before dinitrobenzene sulfonic acid (DNBS) injection with BPA and bacteria treatments.…”
Section: Description Of Work Programmementioning
confidence: 99%
“…In the latest release of the BPA re-evaluation by the European Food Safety Authority (EFSA) in 2023, the tolerable daily intake of BPA for humans was lowered from 4 μg to 0.2 ng per kilogram of body weight per day (kg/bw/day). People with average or high exposure exceed this threshold, indicating health concerns [ 27 ]. The use of BPA is now limited not just in items designed for infants (EU Commission Regulation 2018/213) [ 28 ] but also in other food contact materials and other products, such as thermal paper, where it should not exceed 0.02% by weight [ 22 ].…”
Section: Introductionmentioning
confidence: 99%